Incidence of Garlic common latent virus in Argentina, and phylogenetic and recombination analyses of isolates = Incidência de Garlic common latent virus na Argentina, e análise filogenética e de recombinação de isolados - Torrico Ramallo, Ada Karina; Celli, Marcos Giovani; Conci, Luis Rogelio; Conci, Vilma Cecilia (Embrapa, 2017)
The objective of this work was to estimate the incidence and prevalence of Garlic common latent virus (GarCLV) in the main production regions of garlic (Allium sativum) in Argentina, and to perform phylogenetic and recombination analyses in isolates from these regions. Leaf samples (3,050) were taken from four garlic commercial types, in 13 departments of the four main garlic‑producing provinces of Argentina, in a 1,175‑ha sampling area. Virus infection was evaluated with DAS‑Elisa test using specific antiserum, and the phylogenetic and recombination analyses were done with capsid protein (CP) nucleotide sequence of seven GarCLV isolates from the provinces. The incidence of GarCLV in the evaluated provinces varied between 6.7 and 22% of the samples, whereas the prevalence varied between 52.6 and 70%. In the analysis of garlic commercial types, Morado showed the highest incidence of the virus, in the province of San Juan, whereas Rosado Paraguayo had the lowest incidence, in the province of Cordoba. Nucleotide identity in the CP sequences ranged between 80.3 and 97.6%. The phylogenetic analysis shows the presence of two main groups of GarCLV and of a possible third group that would include only a German isolate. The recombination analysis between isolates from different parts of the world evidences the presence of recombinant isolates from Poland and Australia.